Rural Communities in Transition and Sustainable Regional Development - McKenzie, Fiona Haslam; Hoath, Aileen; Buckley, Amma; Greer, L.; Rolfe, J. (Rural Development Institute, Brandon University, 2013)
Mining and farming have been important industries to the Australian economy since colonial times but the industries have generally operated in separate regions with limited overlaps. Over the last decade mining activity has surpassed agriculture in both return on investment and contribution to gross domestic product (GDP) and farming has continued to lose its share of economic contribution. To date, most mining activity has been in remote and regional areas of Australia where the deposits are richest, but sophisticated extractive processes and high returns are now making deposits viable which hither to have been considered marginal, many of which are in communities where farming has been the main industry. This paper will consider case study sites where mining is increasingly encroaching on what has been traditionally productive farming land. For some communities, mining is welcomed as an important off-farm income, for others, mining is viewed as an environmental and social threat to the agricultural industry. The stresses and strains as well as the opportunities presented by transitional rural economies will be considered.